PENERAPAN TEKNOLOGI INFORMASI DALAM E-TOURISM DANAU BUYAN BERBASIS KEARIFAN LOKAL (E-TOURISM BUYAN, BALI BANGKIT, BALI KEMBALI) - Siti Puspita Hida Sakti MZ; Asslia Johar Latipah; Marzuki Marzuki (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
This research aims to help Bali Kembali based on community empowerment through improving the skills and productivity of the tourism business or Buyan e-tourism based on local wisdom in the village of Pancasari. The purpose of this research is to encourage the empathy of lecturers as researchers and to be able to contribute to solving problems that exist in society. The interaction between students and the community, on the one hand the lecturers get knowledge from the community, and on the other hand the community learns from the lecturer team as researchers to improve their abilities in sustainable development in their region. In this regard, specifically the goal is the development of the capacity, independence, empowerment and productivity of the community in the field of tourism or information technology-based e-tourism based on local wisdom. The results to be achieved from this research are: 1) Increasing the awareness and empathy of lecturers as researchers towards economic, social and cultural issues to be appointed as economic assets so as to increase people's income in order to achieve a more prosperous life; 2) There is a partnership between lecturers who have various skills (administration, education, information technology, etc.) and village partners so that good cooperation can be realized in developing, empowering, and increasing the independence of the tourism business as one of the pillars of the family economy; 3) Increased knowledge of information technology among people who work in the field of tourism or e-tourism in Pancasari Village, Sukasada District, Buleleng Regency, Bali for the success of tourism businesses, so that people continue to get benefits from an economic, social, cultural and welfare perspective; 4) Development of the potential of Buyan Lake as a tourism asset that can make it prosperous and use community stakeholders around Buyan Lake and the people of Pancasari Village.